Utilization of Audio Visual Media to Improve Motivation and Learning Outcomes in Natural Sciences - Harosid, Harun (Scientica Education Journal, 2025)
This study aims to analyze the effect of the use of audio-visual media on students' motivation and learning outcomes in Natural Sciences (IPA) learning. The research method used is the Systematic Literature Review (SLR) approach, with articles selected based on inclusion criteria, such as a focus on the use of audio-visual media in science education, relevance to motivation, and learning outcomes. Articles were obtained from leading academic databases, such as Google Scholar, ERIC, Scopus, and JSTOR. The results of the study indicate that the use of audio-visual media can significantly increase students' learning motivation. This media presents learning materials in a more interesting, interactive, and easy-to-understand way through visual and audio elements. In addition, audio-visual media also has a positive impact on learning outcomes, as seen from the increase in post-test scores which are higher than conventional learning methods. Visualization of abstract concepts through video, animation, and simulation makes it easier for students to understand and remember learning materials. Routine use of audio-visual media is recommended to create a more dynamic and effective learning experience. These findings provide practical recommendations for educators to utilize learning technology in improving the quality of science education. In addition, this study also emphasizes the importance of teacher training in developing and using audio-visual-based learning media so that the results obtained are more optimal.